(untitled) (Asian Journal of Medical and Biological Research, 2015)
Transfection is the most popular experiments among biological scientist to study the gene expression. But it is really tedious to find out the optimum conditions for protein expression for transfection while working with plasmid DNA. In our present study, the main objective was to setup suitable conditions to study the protein expression. From different conditions, protein expression was observed for 2?g of DNA. We tried different cell number and time frame and got 6.25×105cell/ well of 6 well and 24 hour incubation were the best condition for maximum expression of protein. In our experiment 1:3 ratio of DNA: Lipfectamine was the best for optimum expression of protein in mammalian cell line. Asian J. Med. Biol. Res. June 2015, 1(1): 121-129